Fostering Critical Thinking and Analytical Skills in Audit Education - Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The purpose of this study is to explore innovative pedagogical approaches and technological interventions in audit education to foster critical thinking and analytical skills among students. A systematic literature review was conducted to identify key strategies and tools used in audit education, including problem-based learning, case studies, experiential learning, simulation software, and data analytics tools. The findings suggest that these pedagogical approaches and technological innovations play a crucial role in promoting critical thinking skills among audit students by providing them with opportunities for active learning, practical application, and hands-on experience. The implications of this research are significant for both academia and practice. For academia, the findings contribute to the existing body of knowledge by providing empirical support for the effectiveness of various teaching strategies and technologies in audit education. For practice, the insights gained from this study can inform evidence-based practices in audit education and guide educators in selecting the most appropriate methods for fostering critical thinking skills among students. Furthermore, the multidisciplinary perspective adopted in this study facilitates a holistic understanding of the intersection between critical thinking, technology, and audit education, paving the way for further interdisciplinary collaborations and research endeavors.